The impact of relative CEO pay on employee productivity - Aaron Afzali; Lars Oxelheim; Trond Randøy; Jo\~ao Paulo Vieito (Research Institute of Industrial Economics (IFN), 2023)
In this study, we examine the relationship between within-firm pay inequality and employee productivity. We use hand-collected data on a sample of S&P 1500 companies from 2018-2022 and find a concave relationship between the relative CEO pay and employee productivity. Consistent with tournament theory, we show that the pay gap between the CEO and the Vice Presidents initially positively affects employee productivity. However, this positive effect only works up to a certain level, at which - as expressed by the CEO-employee pay ratio - employee discontent initiates a fall in firmlevel productivity. We identify this tipping point as the point at which CEO pay exceeds the median worker's pay by a factor of 40. The average CEO-employee pay ratio in our sample is 193:1, suggesting that most firms could have avoided a fall in productivity by reducing their CEO-employee pay ratio. Our results remain robust after controlling for endogeneity. From a public policy perspective, our findings pave the way for corporate self-regulation of CEO pay to avoid politically imposed hard laws.
Keywords: G18; G32; G34; J24; J33; M12; 330; CEO pay; CEO pay-employee ratio; Employee productivity; Tournament incentives